Foreign direct investment and liberalization policies in Pakistan: An empirical analysis - Rana Ejaz Ali Khan; Qazi Muhammad Adnan Hye (Cogent Economics & Finance, 2014)
To enhance the inflow of foreign direct investment (FDI) and ultimately to increase the economic growth, the countries have implemented a variety of financial and trade liberalization policies in the last three decades. Pakistan also initiated such type of policies. This study makes an analysis of the impact of liberalization (financial and trade) in Pakistan, on the inflow of FDI using the time series data of 1971 - 2009. The DF-GLS test is used to determine the level of integration, and autoregressive distributed lag model to examine the long-run relationship. The results indicate that liberalization indicators, like financial liberalization index and trade openness along with real interest rate, negatively affect the inflow of FDI in Pakistan. Tax revenue of product also negatively affects the FDI. On the other hand, the gross fixed capital formation, infrastructure, and inflation positively influence the FDI in Pakistan. The market size (proxied by real gross domestic product) has shown insignificant effect on FDI.
Keywords: F21; O16; C33; P27; 330; international investment; long-term capital movements; financial markets; saving and capital investment